Electronic polarization effects in the photodissociation of Cl2. - Campbell, E; Alekseyev, AB; Balint-Kurti, G; Brouard, M; Brown, A; Buenker, R; Cireasa, R; Gilchrist, A; Johnsen, A; Kokh, D; Lucas, S; Ritchie, G; et al. (2012)
Velocity mapped ion imaging and resonantly enhanced multiphoton ionization time-of-flight methods have been used to investigate the photodissociation dynamics of the diatomic molecule Cl(2) following excitation to the first UV absorption band. The experimental results presented here are compared with high level time dependent wavepacket calculations performed on a set of ab initio potential energy curves [D. B. Kokh, A. B. Alekseyev, and R. J. Buenker, J. Chem. Phys. 120, 11549 (2004)]. The theoretical calculations provide the first determination of all dynamical information regarding the dissociation of a system of this complexity, including angular momentum polarization. Both low rank K = 1, 2 and high rank K = 3 electronic polarization are predicted to be important for dissociation into both asymptotic product channels and, in general, good agreement is found between the recent theory and the measurements made here, which include the first experimental determination of high rank K = 3 orientation.